Optical neuronavigation without rigid head fixation during awake surgery - Freyschlag, Christian F.; Kerschbaumer, Johannes; Eisner, Wilhelm; Pinggera, Daniel; Brawanski, Konstantin Robert; Petr, Ondra; Bauer, Marlies; Grams, Astrid E.; Bodner, Thomas; Seiz-Rosenhagen, Marcel; Thomé, Claudius (World neurosurgery, 2017)
Objective: Optical neuronavigation without rigid pin fixation of the head may lead to inaccurate results because of the patient's movements during awake surgery. In this study, we report our results using a skull-mounted reference array for optical tracking in patients undergoing awake craniotomy for eloquent gliomas. Methods: Between March 2013 and December 2014, 18 consecutive patients (10 men, 8 women) with frontotemporal (n = 16) or frontoparietal (perirolandic; n = 2) lesions underwent awake craniotomy without rigid pin fixation. All patients had a skull-mounted reference array for optical tracking placed on the forehead. Accuracy of navigation was determined with pointer tip deviation measurements on superficial and bony anatomic structures. Good accuracy was defined as a tip deviation <2 mm. Results: Gross total resection (>98%) was achieved in 7 patients (38%); >90% of tumor was resected in 8 patients (44%). In 3 patients, only subtotal resection or biopsy was performed secondary to stimulation results. In all patients, good accuracy of the optical neuronavigation system could be demonstrated without intraoperative peculiarities or complications. The reference array had to be repositioned because of loosening in 1 patient. Neuronavigation could be reliably applied to support stimulation-based resection. Conclusions: A skull-mounted reference array is a simple and safe method for optical neuronavigation tracking without rigid pin fixation of the patient's head.